2010
DOI: 10.1016/j.ejvs.2010.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Surgical Procedures for Hind Limb Ischaemia Mouse Models Result in differences in Collateral Formation

Abstract: The extent of the arterial injury is associated with different patterns of perfusion restoration. The double coagulation mouse model is, in our hands, the best model for studying new therapeutic approaches as it offers a therapeutic window in which improvements can be monitored efficiently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
110
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(112 citation statements)
references
References 28 publications
2
110
0
Order By: Relevance
“…Additionally, previous studies have shown that the therapeutic window ranges from 1 to 3 weeks, with complete blood flow recovery in untreated control animals after these time points (Hellingman et al, 2010). Therefore, we used a single administration to analyze the effect on neovascularization.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, previous studies have shown that the therapeutic window ranges from 1 to 3 weeks, with complete blood flow recovery in untreated control animals after these time points (Hellingman et al, 2010). Therefore, we used a single administration to analyze the effect on neovascularization.…”
Section: Discussionmentioning
confidence: 99%
“…Double electrocoagulation of both the common femoral artery and the popliteal artery distally was performed because it could provide a larger therapeutic window (Hellingman et al, 2010). This enables a better analysis of the enhancing effects of MC-shPHD2 on arteriogenesis.…”
Section: Surgical Procedures To Induce Hindlimb Ischemiamentioning
confidence: 99%
See 2 more Smart Citations
“…Hind limb ischemia was induced as described before (Hellingman et al, 2010;Bastiaansen et al, 2013). Briefly, animals were sedated with an intraperitoneal injection of 5 mg/kg Dormicum, 0.5 mg/kg Domitor, and 0.05 mg/kg Fentanyl.…”
Section: Animal Modelmentioning
confidence: 99%